'This disease is not meant for the hospital, it is Asram': Implications of a traditionally-defined illness on healthcare seeking for children under-5 in rural Ashanti, Ghana. - Princess Ruhama Acheampong; Aliyu Mohammed; Sampson Twumasi-Ankrah; Augustina Angelina Sylverken; Michael Owusu; Emmanuel Acquah-Gyan; Timothy Kwabena Adjei; Easmon Otupiri; Ellis Owusu-Dabo (PLOS Global Public Health, 2022)
Every child has the right to survive, grow and develop. However, in spite of the considerable global gains that have been made in child survival, Sub-Saharan Africa still has the highest child mortality rates and accounts for the greatest burden of mortality globally. The majority of these children die without ever reaching a health facility. The practice of appropriate healthcare-seeking behaviour has a great potential to reduce the occurrence of severe and life-threatening childhood illnesses. Several factors, however, influence healthcare-seeking behaviour, including perceptions of the cause of illness and socio-cultural perspectives. This study seeks to understand local concepts of a traditionally-defined illness complex, Asram, and its influence on healthcare seeking behavior of mothers/caregivers. This qualitative study was conducted from October 2019 to February 2020. Four Focus Group Discussions were conducted with mothers/caregivers of children under-5 and 22 Key Informant Interviews with mothers/caregivers of children who had Asram, health workers at district, facility, and community levels, and Asram healers. Participants were selected from two rural communities, Akutuase and Wioso of the Asante Akim North district in the Ashanti region of Ghana. Data analysis was carried out iteratively throughout data collection, using a thematic analysis approach. The study shows that Asram is a childhood illness complex that is perceived to have been acquired spiritually and/or inherited. Nine types of Asram were described. This childhood illness was said to be treatable by Asram healers who had sub-specialties in treatment approaches that were determined by the Asram type reported. Mothers/caregivers trusted Asram healers and preferred to call on them first. This was found to be the main reason for delays in seeking healthcare for children under-5 who showed symptoms of Asram. Asram is a childhood illness complex that is believed to be better managed outside the health facility setting. This study complements existing knowledge and creates opportunities for further research and the introduction of more effective interventions in the effort to improve child survival in rural communities.